2009
DOI: 10.3949/ccjm.75a.08011
|View full text |Cite
|
Sign up to set email alerts
|

Depression and heart disease: What do we know, and where are we headed?

Abstract: Depression and heart disease have an intricate association and perhaps a causal relationship. We review the current status of depression and heart disease and provide an algorithm for diagnosing and treating depression in cardiac patients that internists and cardiologists can use in their daily patient encounters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 139 publications
1
83
0
1
Order By: Relevance
“…7 Studi INTERHEART di 52 negara didapatkan faktorfaktor psikososial, antara lain stres dan depresi merupakan faktor risiko infark miokardium 32,5%. [8][9][10] Untuk mengurangi risiko gangguan kardiovaskular itu diperlukan pemeriksaan dini fungsi endotel.…”
Section: 2unclassified
“…7 Studi INTERHEART di 52 negara didapatkan faktorfaktor psikososial, antara lain stres dan depresi merupakan faktor risiko infark miokardium 32,5%. [8][9][10] Untuk mengurangi risiko gangguan kardiovaskular itu diperlukan pemeriksaan dini fungsi endotel.…”
Section: 2unclassified
“…Many studies suggested that the prevalence of depression is higher among patients with CHD compared to people without CHD [1][2][3][4]. However, a study showed that depression was not associated with developing CHD [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study mentioned that depression is a risk factor for CHD and it can result in complications and death [4]. Furthermore, recent studies have shown much evidence that depression is a risk factor for developing CHD, with an approximately 2-times higher risk of death [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Such alterations are believed to reduce heart rate variability (HRV), a well-known prognostic risk factor for cardiovascular disease and mortality. [2] Access this article online Autonomic function assessment by HRV is relatively new and not used in clinical practice in most of the medical setups in India. Very few studies have been carried out to assess cardiac autonomic functions in depressed patients in Indian population.…”
Section: Introductionmentioning
confidence: 99%